FENOMENA LARANGAN PERKAWINAN SEMARGA PADA RUMPUN MARGA NARASAON DI DESA PARSAORAN SIBISA KECAMATAN AJIBATA KABUPATEN TOBA - Soniya Rosalina; Malau, Waston (Institut Agama Islam Ngawi, 2024)
Abstract: This research aims to explore the background to the return of the ban on marriage in the Narasaon clan, describe concerns regarding marriage in the Narasaon clan, and describe the process of the return of the ban on marriage. The method used in this research is qualitative with a descriptive approach. This research was conducted in Parsaoran Sibisa Village, Ajibata District, Toba Regency. Data collection techniques through interviews and documentation. The results of the research show that the prohibition on marriage between theNarasaon clan is because the results of marriages within the Narasaon clan will not go well and will not produce offspring, so the prohibition on marriage between the Narasaon clan is maintained. This forbidden marriage took place in Parsaoran Sibisa Village, this happened because the perpetrator no longer believed in the beliefs regarding the prohibition of intermarriage in the Narasaon clan.Kata Kunci: Same Clan Marriage, Narasaon, Parsaoran Sibisa